Genotype x environment interaction for corn oil content in different fertilizing and seasons - Weder Ferreira dos SANTOS; Flávio Sérgio AFFÉRRI; Joênes Mucci PELÚZIO; Rafael Marcelino da SILVA; Lucas Alves de FARIA; Layanni Ferreira SODRÉ (Journal of Bioenergy and Food Science, 2018)
The genotypes present differential behavior as a function of genotype x environment interaction, having an effect on heritability estimation and selection gain. Thus, the present study was carried out with the objective of studying the interaction genotype x environment, for oil content in corn grains, as a function of nitrogen doses and sowing times. In the agricultural year 2015/16, six competition trials of maize genotypes were carried out in Palmas-TO, three of which were installed on 12.01.2015 and three on 01.01.2016. The trials were installed at two sowing times, and in each season, the genotypes were cultivated under conditions of low, medium and high nitrogen in coverage. The experimental design used in each trial was randomized blocks with 12 genotypes and three replicates. Analyzes of adaptability, stability, stratification and environmental dissimilarity were performed. The genotype GEN 12 is potentially promising for the oil content, being considered ideal by the methodology of Eberhart & Russel (1966). Evaluations of maize genotypes, carried out at different times under the same fertilization dose, provide similar results.